(untitled) (Buletin Nutrisi dan Makanan Ternak, 2022)
This study aims to determine crude protein and crude fiber content of silage complete feed-based hyacinth (Eichornia crassipes). This study was designed based on a completely randomized design with 4 treatments 4 replications. Treatment P0 = fermented 0 days, P1 = fermented 10 days, P2 = fermented 20 days, P3 = fermented 30 days. The results showed an average of crude protein content is P0 = 11.96%, P1 = 12.97%, P2 = 14.68%, and P3 = 12,76% and crude fiber is P0 = 21.88%, P1 = 24.36%, P2 = 22.91% and P3 = 24.62%. Conclusion of fermented in silage complete feed-based hyacinth significantly affects crude protein and crude fiber silage complete feed. The best fermentation time is 20 days because it has the highest crude protein and crude fiber lows. Keywords: Hyacinth, crude protein, crude fiber, and complete feed silage.